Syphilitic Balanitis of Follmann, A Rare Case Report - Agarwal, Pooja; Jagati, Ashish; Vadher, Priyanka; Chaudhary, Malay (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Syphilitic balanitis of Follmann is a rare presentation of primary syphilis. It can occur before or after the appearance of primary chancre and some time without any associated primary chancre. We are reporting a case of syphilitic balanitis of Follmann, in a 23 years old heterosexual male, who presented with balanitis associated with single indurated lesion over coronal sulcus and few superficial ulcers over prepuce.